Pengaruh Profitabilitas,Pertumbuhan Laba, dan Leverage terhadap Kualitas Laba pada Perusahaan Sektor Industrial di BEI - Annis Sa’adah; Isyfa Fuhrotun Nadhifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the effect of profitability, earnings growth, and leverage on earnings quality in industrial sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research adopts a quantitative approach using secondary data from annual financial statements. The sampling technique employs purposive sampling, resulting in 39 companies with a total of 117 observations. The analysis method used is multiple linear regression with classical assumption tests. The analysis indicates that profitability, earnings growth, and leverage are associated with earnings quality, while the coefficient of determination suggests that the model has limited explanatory power in explaining variations in earnings quality, indicating the presence of other influencing factors and providing opportunities for future research. This study implies that companies need to maintain financial performance consistency and manage their capital structure effectively to support earnings quality, and it contributes empirical evidence from the industrial sector, which is characterized by high capital intensity and operational complexity, thereby enriching the literature on earnings quality determinants.